2016
DOI: 10.1186/s12934-016-0588-2
|View full text |Cite|
|
Sign up to set email alerts
|

Fermentative production and direct extraction of (−)-α-bisabolol in metabolically engineered Escherichia coli

Abstract: Background(−)-α-Bisabolol, also known as levomenol, is an unsaturated sesquiterpene alcohol that has mainly been used in pharmaceutical and cosmetic products due to its anti-inflammatory and skin-soothing properties. (−)-α-Bisabolol is currently manufactured mainly by steam-distillation of the essential oils extracted from the Brazilian candeia tree that is under threat because its natural habitat is constantly shrinking. Therefore, microbial production of (−)-α-bisabolol plays a key role in the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 40 publications
2
46
0
2
Order By: Relevance
“…For example, increasing idi copies enhanced (–)‐α‐bisabolol production in E. coli (Han et al . ), replacing the native promoter of the MEP pathway genes (including dxs ) with the strong bacteriophage T5 promoter resulted in the production of β‐carotene at high titres (6 mg g −1 dry cell weight) (Yuan et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing idi copies enhanced (–)‐α‐bisabolol production in E. coli (Han et al . ), replacing the native promoter of the MEP pathway genes (including dxs ) with the strong bacteriophage T5 promoter resulted in the production of β‐carotene at high titres (6 mg g −1 dry cell weight) (Yuan et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…IspA is also considered to be a key enzyme for terpenoids biosynthesis (Han et al, 2016), however ispA is not used extensively with MEP pathway genes but is widely used in the MVA pathway. Combination of dxs, idi and ispA can increase squalene production in YSS12 by up to 71-fold when compared with the strain that only harbors two copies of SQS.…”
Section: Discussionmentioning
confidence: 99%
“…DXS and IDI have been reported as the keyenzymes in the MEP pathway for increasing terpenoid production in E. coli (Yuan et al, 2006; and squalene production (Ghimire et al, 2009). Overexpression of genes dxr (Lv et al, 2016), ispDF Yuan et al, 2006), ispG (Liu et al, 2014) and ispA (Han et al, 2016) were able to enhance terpenoids production. On the contrary, other studies have shown that overexpression of dxr coupled with dxs produced a similar isoprene level when compared with the dxs overproduction strain (Xue and Ahring, 2011), and overexpression of ispDF together with dxs and idi resulted in decrease in terpenoids production (Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, this separation step could be bypassed by choosing solvents compatible with the final product formulation. Examples include the use of methyl oleate or isopropyl myristate in the production of amorphadiene, canola oil in the production of the sesquiterpene alcohol bisabolol, and farnesene as solvent in the production of the monoterpene limonene …”
Section: Introductionmentioning
confidence: 99%
“…As a result, the product is not a homogeneous continuous phase but a stable emulsion. Although the formation of sesquiterpene emulsions is usually not mentioned in laboratory‐scale studies, this problem has been reported at larger scales . Reported recovery methods include inducing phase inversion and obtaining an emulsion of water in a continuous oil phase (w/o), which is separated afterwards by centrifugation.…”
Section: Introductionmentioning
confidence: 99%